2008
DOI: 10.1016/j.jeem.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Reformulating competition? Gasoline content regulation and wholesale gasoline prices

Abstract: The 1990 Clean Air Act Amendments stipulated gasoline content requirements for metropolitan areas with air pollution levels above predetermined federal thresholds. The legislation led to exogenous changes in the type of gasoline required for sale across US metropolitan areas. This paper uses a panel of detailed wholesale gasoline price data to estimate the effect of gasoline content regulation on wholesale prices and price volatility. We investigate the extent to which the estimated price effects are driven by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Given US non-California 2008 summer gasoline consumption of 47 billion gallons and a $0.01-$0.015 per gallon price effect estimated in Brown et al (2008), the VOC standards imposed by these regulations increase US annual gasoline expenditures by $524-$784 million.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given US non-California 2008 summer gasoline consumption of 47 billion gallons and a $0.01-$0.015 per gallon price effect estimated in Brown et al (2008), the VOC standards imposed by these regulations increase US annual gasoline expenditures by $524-$784 million.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting "patchwork" of regulation prevents gasoline transporters from arbitraging price differences across areas with different gasoline standards. Several recent papers-Jennifer Brown et al (2008), Ujjayant Chakravorty, Céline Nauges, and Alban Thomas (2008), and Erich Muehlegger (2006)-have found that this market segmentation significantly increases both gasoline price levels (beyond the increase in production cost) and price volatility. The US Congress, concerned about the price effects of segmented gasoline markets, inserted language into the Energy Policy Act of 2005 (section 1541(b)) that constrained the ability of the EPA to enact or approve new gasoline standards that could exacerbate segmentation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chouinard and Perloff (2007) note that retail and wholesale gasoline prices vary over time and across geographic locations due to differences in government policies and other factors that affect demand, costs, and market power. Brown et al (2008) examine wholesale gasoline market integration in the presence of changes in the number of competitors contrasted with geographic market segmentation induced by regulation. Further valuable insights are provided by Deltas (2008), Alm et al (2009), Kendix and Walls (2010), Marion and Muehlegger (2011) among others.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies that focus on this effect are Brown, Hastings, Masur & Villa-Boas (2008) and Chakravorty, Naughes & Thomas (2008). Although each uses different methods, they both find that prices rise when environmental standards isolate markets.…”
mentioning
confidence: 99%